2018
DOI: 10.1002/tesj.393
|View full text |Cite
|
Sign up to set email alerts
|

Peer collaborative writing in the EAP classroom: Insights from a Canadian postsecondary context

Abstract: Peer collaborative second language (L2) writing has recently gained a lot of traction (Hu & Lam, 2009; Swain & Lapkin, 2013) as both instructors and students recognize its advantages. Although research on peer feedback in L2 contexts has a long history, peer collaborative L2 writing research has been sparse. This article reports on a study that investigated student perceptions on collaboration in an extended, take‐home writing assignment in an English for academic purposes context at a Canadian university. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 21 publications
5
20
0
Order By: Relevance
“…This was evidenced by their increased scores in the posttest writing. The finding is congruent with previous studies (e.g., Bhowmik et al, 2019;Coffin, 2020;Storch, 2011;Wang, 2019), which claimed that CW can provide opportunities for learners to brainstorm for ideas and give feedback that can improve the quality of writing.…”
Section: Figure 6 Goals Of Individual Members Towards Cw Taskssupporting
confidence: 90%
See 2 more Smart Citations
“…This was evidenced by their increased scores in the posttest writing. The finding is congruent with previous studies (e.g., Bhowmik et al, 2019;Coffin, 2020;Storch, 2011;Wang, 2019), which claimed that CW can provide opportunities for learners to brainstorm for ideas and give feedback that can improve the quality of writing.…”
Section: Figure 6 Goals Of Individual Members Towards Cw Taskssupporting
confidence: 90%
“…Sociocultural theory has been emphasized over the last two decades, in particular CW (Bhowmik et al, 2019;Doboa, 2014;Li, 2014;Li & Kim, 2016;Lowry, Curtis, & Lowry, 2004;Storch 2002Storch , 2004Storch , 2011Storch , 2013Zhang, 2018). Sociocultural theory-based initiatives make learning activity more dynamic and interactive, and learning and development encourages collaboration and interaction among learners (Vygotsky, 1978;Lantolf & Thorne, 2007).…”
Section: Theoretical Perspective Of Collaborative Writingmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, students writing outcomes showed that students performed better outcomes in content quality and organization with the aid of the system. Bhowmik et al ( 2019 ) also reported benefits of students’ collaboration, including raising critical awareness about language practice in academic writing, which led to an enhanced understanding of the meaning-making processes in text construction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Collaborative writing is not without shortcomings despite learning contributions. Bhowmik et al ( 2019 ) explain challenges identified within a Canadian post-secondary context includes learners’ unfamiliarity with peer collaboration, absence of clear guidelines regarding the steps to be followed, inadequate proficiency levels within groups, and group members’ different experiences, which can cause struggle in communication among partners. A qualitative study by Such ( 2019 ) investigated how post-secondary EFL learners work collaboratively to complete online writing assignments using wikis.…”
Section: Literature Reviewmentioning
confidence: 99%